Oranges and sunshine based on a true story - Gerrard, Lisa 1961- (Icon Home Entertainment, 2011)
Oranges and Sunshine tells the story of Margaret Humphreys, a social worker from Nottingham, who uncovered one of the most significant social scandals in recent times: the forced migration of children from the United Kingdom. Almost singlehandedly, against overwhelming odds and with little regard for her own well-being, Margaret reunited thousands of families, brought authorities to account and worldwide attention to an extraordinary miscarriage of justice. She discovered a secret that the British government had kept hidden for years: one hundred and thirty thousand children in care had been sent abroad to commonwealth countries, mainly Australia. Children as young as four had been told that their parents were dead, and been sent to children's homes on the other side of the world. Many were subjected to appalling abuse. They were promised oranges and sunshine, they got hard labour and life in institutions. ... (Covertext) ; en
Orig.: Grossbritannien/Australien, 2010
Bildformat 2.35:1 (16:9 anamorph)
Extras: Audio commentary: Jim Loach (director), Rona Munro (writer). - Documentaries: 'Stolen Childhoods: A Nation says Sorry'. - Interviews: Emily Watson & Hugo Weaving. - Q&A at the British Film Institute with Jim Loach, Rona Munro, Margaret Humphreys and Emily Watson. - Archive Photo Gallery
Keywords: Skandal; Rechtsbeugung; Deportation; Fremdunterbringung; Kind; Öffentliche Erziehung; Großbritannien; Australien; DVD-Video